Innovation In The Procurement Of Government Goods And Services In Order To Increase The Tax Compliance Intention Of MSME Actors - Khusnaini, Khusnaini; Liyana, Nur Farida; Hermawan, Irwan (Balance Vocation Accounting Journal, 2025)
The participation of MSMEs in government procurement of goods and services has been running since 2015, but there are still a number of obstacles in its implementation. MSMEs contribute around 60% of Gross Domestic Product (GDP) and absorb more than 97% of the workforce in Indonesia. This great potential makes the involvement of MSMEs in government procurement of goods and services an important strategy to drive the economy. In addition to playing a role in the procurement of goods and services, MSMEs are also expected to contribute to state revenues through taxes. Through the Business Development Services (BDS) program, the Directorate General of Taxes seeks to assist MSMEs in developing their businesses and increasing tax awareness. In 2024, the Central Jakarta Regional Office of the Directorate General of Taxes will hold a PBJ innovation program integrated with the BDS program, it is hoped that MSMEs can be more independent in managing their financial administration and taxation, so that they can gradually increase their tax contribution to the state. Using the Participatory Action Research method, this research aims to analyze the PBJ innovation carried out by the Central Jakarta Regional Office of the Directorate General of Taxes in increasing tax compliance of MSMEs in Indonesia. The results of the study indicate that the PBJ-BDS innovation is capable of increasing tax awareness and compliance among MSMEs, as well as encouraging independence in financial and tax administration management. This strategy not only strengthens the position of MSMEs in government procurement, but also contributes to state revenue and the sustainability of MSME businesses in Indonesia. This research is expected to contribute to the development of more adaptive and innovative policies so that PBJ innovation can become an effective instrument in encouraging MSMEs to comply with tax regulations, as well as creating a more stable, competitive, and equitable economic ecosystem in Indonesia.